The Mythologem of Water in A. Varlamov’s Story Rafting - Natalia V. Kovtun; Elizaveta O. Novikova (Гуманитарный вектор, 2023)
The article analyzes the mythologem of water – a phenomenon that has become particularly popular in the art and artwork of the XX–XXI centuries, which is associated with a breakdown of the previous cultural paradigm, the need for a new view of the world and man, the actualization of interest in the archaic, the links of artistic words and neomythological imagery. The object of the research is Alexei Varlamov’s novel Rafting as an indicative text that reveals this issue. The subject of analysis is the mythologeme of "water" and its artistic representation in the novel in all its variety of meanings: the primary element of being, the border between worlds, the space of initiation, the labyrinth, a special entity whose existence is inseparable from the history of man and mankind. The aim of the study is to analyze the artistic representation of the mythologem of water in the prose of A. Varlamov. Varlamov’s key story Rafting through the prism of which the fundamental changes in the relationship between man and nature, characteristic of the current literature in general are evident. Water images (river, rain, well, sea monster) are used in the text to reveal the inner world of heroes whose fate reflects the history of mankind: from paradise times, through love, temptations (stages of initiation) to the knowledge of the tragedy of being and mortality. Water, traditionally signifying the border between worlds, becomes an exit to otherness, the characters’ own subconsciousness (the motif of the labyrinth), where everyone is destined to meet a "double", a monster, the battle with which determines insight, approaching the mystery of existence. The emphasis on internal, psychological experiences mediated by the water element forces the reader to turn to the mythopoetic layer of culture, reminds of the archetypal universal. The methodology and methods of research are defined by mythopoetic analysis, a structural-systemic approach to the material and cultural-historical analysis. The practical significance of the work is the possibility of using research materials in teaching such courses as "History of Russian Literature", "Comparative Studies", "Culturology". The mythologeme of water unfolds as one of the key in the work of a number of contemporary authors, representing the natural philosophical direction within modern traditionalism (V. Rasputin), neo-traditionalism (R. Senchin, M. Tarkovsky), developing ecological prose, starting with the texts by V. Astafiev. It is important to show how A. Varlamov’s neo-myth fits into the designated artistic field, what is its fundamental novelty, and how the author continues already established artistic traditions.